(untitled) (Acta Entomologica Serbica, 2018)
On 02.12.2017, Oscar C. B. Neto was able to make an interesting observation in his backyard in Benedito Novo, Santa Catarina, Brazil: Two different colour morphs of Stiretrus decemguttatus could be photographed while they were mating and feeding at the same time (Fig. 1). One specimen was feeding on a larva, while the other one was feeding on an Asopine, probably another colour morph of S. decemguttatus or a specimen of S. erythrocephalus. Both species have similar blue colour patterns which differ in tibial expansions and median abdominal spine (Thomas, 1992), characters which are not visible in Figure 1.